Tafsir Tarbawi in Indonesia: Efforts to Formulate Qur’an-Based Islamic Education Concept - Cucu Surahman (Jurnal Pendidikan Islam, 2019)
This article examines the interpretation of the Qur’an among education scholars in contemporary Indonesia. This article studies 24 books of Tafsir Tarbawi (educational exegesis) which has been written in 2000-2018. The study focuses on the nature, validity, and contribution of Tafsir Tarbawi in Indonesia. This research belongs to library research. By using bibliographical analysis, this study concludes that firstly, Tafsir Tarbawi is a Qur’anic exegesis that uses pedagogic approach in interpreting the Qur’an; secondly, it appears as a text book and as a special work of tafsir; thirdly, it is a valid and acceptable Qur’anic exegesis; and fourthly, its works have relatively contributed to the development of Islamic Education science, either in term of paradigm and method or in that of product. As a paradigm and methodology, books of Tafsir Tarbawi have offered approach and method of tafsir in developing Tafsir Tarbawi (pedagogic exegesis), while as a product, book of Tafsir Tarbawi in Indonesia not only have confirmed basic concepts and principles of Islamic Education, but also have formulized science or theory of Islamic Education. Therefore, Tafsir Tarbawi might function as theological-scriptural basis and epistemological-conceptual tool as well. However, these efforts should be advanced.